Controlled Release of Stem Cell Secretome Attenuates Inflammatory Response against Implanted Biomaterials. Issue 12 (18th May 2020) - Mohammadi, Mohammadreza; Luong, Jennifer Cam; Rodriguez, Samuel Mathew; Cao, Rui; Wheeler, Ashlyn Elizabeth; Lau, Hien; Li, Shiri; Shabestari, Sepideh Kiani; Chadarevian, Jean Paul; Alexander, Michael; de Vos, Paul; Zhao, Weian; et al.
Abstract: Inflammatory response against implanted biomaterials impairs their functional integration and induces medical complications in the host's body. To suppress such immune responses, one approach is the administration of multiple drugs to halt inflammatory pathways. This challenges patient's adherence and can cause additional complications such as infection. Alternatively, biologics that regulate multiple inflammatory pathways are attractive agents in addressing the implants immune complications. Secretome of mesenchymal stromal cells (MSCs) is a multipotent biologic, regulating the homeostasis of lymphocytes and leukocytes. Here, it is reported that alginate microcapsules loaded with processed conditioned media (pCM‐Alg) reduces the infiltration and/or expression of CD68+ macrophages likely through the controlled release of pCM. In vitro cultures revealed that alginate can dose dependently induce macrophages to secrete TNF α, IL‐6, IL‐1 β, and GM‐CSF. Addition of pCM to the cultures attenuates the secretion of TNF α ( p = 0.023) and IL‐6 ( p < 0.0001) by alginate or lipopolysaccharide (LPS) stimulations. Mechanistically, pCM suppressed the Nf κ B pathway activation of macrophages in response to LPS ( p < 0.0001) in vitro and cathepsin activity ( p = 0.005) in response to alginate in vivo. These observations suggest the efficacy of using MSC‐derived secretome to prevent or delay the host rejection of implants. Abstract : Inflammatory response against biomaterials have hampered their long‐term benefit. Loading condition media of mesenchymal stem cells into alginate microcapsules (pCM‐Alg) reduce the inflammatory response against alginate. Mechanistically, alginate upregulates the production of IL‐6, TNF α, and GM‐CSF in the macrophages, and MSC condition media inhibits these cytokines likely through Nf κ B pathway.